AVALIAÇÃO DOS INDICADORES EPIDEMIOLÓGICOS PARA A HANSENÍASE NO BRASIL, 2008 A 2015 - EVALUATION OF EPIDEMIOLOGICAL INDICATORS FOR LEPROSY IN BRAZIL, 2008 - 2015 - Luís Pedro Ferreira de Assis; Andressa Meline Cozer; Vitória Castilho Amâncio; Annah Rachel Graciano; Divanita Cândida da Silva Dias (UniEVANGÉLICA, 2017)
Objective: To verify the prevalence rate and specific mortality of leprosy in Brazil and its regions and correlate the prevalence rates for female and male. Methods: analytical ecological study with temporal trend of design. They were used as data sources SIH, SIM and IBGE. The population corresponded to the total number of new reported cases and who were diagnosed with leprosy between 2008 and 2015. Results: there is a reduction in prevalence rates in the country, reported cases of leprosy in the general population between the years 2008 and 2015. There was a significant reduction in the number of deaths from leprosy. In the evaluated group, the prevalence of leprosy has increased in some regions of Brazil after several consecutive years of gradual decline. Conclusions: It is worth emphasizing the importance of studies on the prevalence of leprosy in Brazil, mainly in the Midwest, where the prevalence has increased significantly in recent years, especially in the state of Mato Grosso. It is essential to the development of public policies and the creation of specific protocols for the diagnosis and treatment of patients, considering its history and its social consequences, reinforcing the importance of proper conduct in the management of these patients.